Impact of Covid-19 Outbreak on Health Care Professionals in Ghana: A Study at Greater Accra Regional Hospital. - Prempeh, Y. A. (University of Ghana, 2023)
The outbreak of the novel corona virus (COVID-19) stretched the capacity of health services to its limits and its effect on health care professionals have been reported by several studies. The review of literature showed that there is paucity of empirical investigations on the experience of health professionals in Africa and Ghana. Therefore, this study sought to examine the impact of COVID-19 outbreak on healthcare professionals in Greater Accra Regional Hospital. The cross-sectional design was employed and the respondents selected using simple random sampling. The study considered 424 healthcare professionals at Greater Accra Regional Hospital. The healthcare professionals included nurses, general physicians (doctors), physician assistants, midwives and laboratory technicians. The data was gathered from the respondents using a self-administered and structured questionnaire. The data from the respondents was entered into SPSS version 21 where descriptive and inferential statistics were computed. The study findings reported adverse psychological outcomes in the form of extreme severe depression and anxiety and severe stress. The majority of the respondents exhibited moderate adverse mental behaviours in the form of moderate intrusion, hyper-arousal and avoidance behaviour. It was identified that most of the healthcare professionals received social support from “family, friends and significant others”. It is recommended that psychological and mental health support should be provided to all healthcare professionals by clinical psychologist. The study also proposes that fortnight monitoring and evaluation of frontline workers to identify signs of adverse psychological and mental effect and offer immediate treatment.
MSc. Monitoring and Evaluation
Keywords: COVID-19; health services; Greater Accra Regional Hospital; Ghana